Making Globalization Work for All. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This paper focuses on concerns over wages, jobs, and future prospects are real and pressing for those who are not well equipped to thrive in this new world. History clearly tells us that closing borders or increasing protectionism is not the way to go. Many countries have tried this route, and just as many have failed. Instead, we need to pursue policies that extend the benefits of openness and integration while alleviating their side effects. Emerging and developing economies have been the prime beneficiaries of economic openness. According to the World Bank, trade has helped reduce by half the proportion of the global population living in extreme poverty. China, for instance, saw a phenomenal drop in its extreme poverty rate-from 36 percent at the end of the 1990s to 6 percent in 2011. Another example is Vietnam, which-in a single generation-moved from being one of the world's poorest nations to middle-income status-which has allowed for increased investments in health and education.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet